1991
DOI: 10.1007/bf01319706
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and burrowing ecology of two East African mangrove crabs

Abstract: Abstract. The behavior and ecology of two mangrove crabs, Sesarma meinerti De Man, 1887 and Cardisoma carnifex (Herbst, 1794) were investigated at the beginning of the rainy season (October-November 1988) at Mida Creek, Kenya. Both species occupy upper intertidal levels, above mean high-water neap, and completely overlap in their zonation. Each burrow lasts ca. 3 wk, with no significant difference between the species. Both are more active around dusk and dawn and also follow a similar trend in their foraging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
6

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 34 publications
3
62
0
6
Order By: Relevance
“…Both crabs showed leaf preference because of the flora associated to their habitat, they showed high level of omnivorous feeding habit, as shown in the stomach content analysis indicated that they both feed on plant materials, crustaceans, fish fragments (bone and scales), sand grains and unidentified items, this support the work of Micheli [13] for Cardiosoma carnifex and Sesarma mainerti. Fish fragments and crustacean found in their stomach content was attributed to the inter migration to shallow part of coastal water.…”
Section: Discussionsupporting
confidence: 70%
“…Both crabs showed leaf preference because of the flora associated to their habitat, they showed high level of omnivorous feeding habit, as shown in the stomach content analysis indicated that they both feed on plant materials, crustaceans, fish fragments (bone and scales), sand grains and unidentified items, this support the work of Micheli [13] for Cardiosoma carnifex and Sesarma mainerti. Fish fragments and crustacean found in their stomach content was attributed to the inter migration to shallow part of coastal water.…”
Section: Discussionsupporting
confidence: 70%
“…Impeded microflora and macroinvertebrate colonisation due to deforestation subsequently impairs degradation processes. Mangroves modify physico-chemical parameters (Bosire et al, 2003) and create a variety of microhabitats besides providing many food materials, which encourage faunal colonisation (Macnae and Kalk, 1962;Macnae, 1968;Micheli et al, 1991;DahdouhGuebas et al, 1999). The modified physico-chemical conditions and macroinvertebrate colonisation seem to support higher weight loss rates in treatments with mangrove cover as compared to bare treatments (Camilleri, 1992;Benner and Hodson, 1985;Steinke et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Verwey, 1929;Gerlach, 1958;Macnae, 1968). More recent ecological studies mainly deal with burrowing crabs from the intertidal (Dye and Lasiak, 1986;Robertson, 1986;Warren and Underwood, 1986;Macintosh, 1988;Robertson and Daniel, 1989;Micheli et al, 1991;Smith et al, 1991). Burrow construction and maintenance, ventilation and import of organic matter may play a significant role in the energy flow and element cycling in shallow coastal systems (for a review with respect to tropical ecosystems see Alongi, 1989).…”
Section: Introductionmentioning
confidence: 99%